Qhapaq ñan world heritage, Socoroma-Zapahuira section and mobility systems in the transboundary andean landscape (700-2021) - Balcarce Villanueva, Esteban (2021)
This study begins with a field visit and starts from the beginning, that recording is another way to conserve, pursues the hypothesis that in a limited space in the foothills of the Arica and Parinacota region, there are several urban and territorial mobility systems at different speeds, cultures and times, having in common the pre-Andean landscape of the Andes that welcomes them and the fact that it is in full force to date, highlights the importance and characteristics of the Qhapaq Ñan (main road), an international highway that joins Chile and Bolivia, and an airfield in the same area crossing the discussion of the "Heritage", on the good, investigating the theory of monuments, arriving at new expansions of the concept. A qualitative methodology is used within the interpretive paradigm on a territorial scale, and it is concluded with a record of high technological resolution, delivering from it, a relationship that interprets the place from mobility with emphasis on the existence of the Qhapaq Ñan today Heritage of the Humanity (2014).